Green Accounting Analysis in Public and Private Hospitals - Sri Madona Saleh; Elfina Yenti; Atika Amor (Akuntansi dan Manajemen, 2023)
This study aims to determine the applicationof environmental prevention costs, environmental detection costs, internal environmental failure costs and external environmental failure costs in public and private hospitals in Batusangkar. The type of research used is a field research using quantitative methods to see how enviromental accounting is applied in public and private hospitals in Batusangkar. The results of this study indicate that the Hanafiah Hospitals has implemented IPAL properly in accordance with the Minister of Environment Regulation No. 11 of 2020 PP of 2021 but not all categories of Enviromental costs according to Hansen Mowen issued by the RSUD. While at the Harapan Ibunda Hospitals also has its own IPAL facility to manage its waste according the Minister of criteria only the city goverment in the relevant sector conducts an evaluation.